Macroeconomic impact on stock returns in the Croatian hospitality industry - Bogdan, Siniša (Array, 2019)
Tourism is one of the most important sectors in the Republic of Croatia. It plays a significant role in its economic development. This research investigates whether the macro-variables have an impact on the stock returns in the hospitality industry. The focus of the work consists in causality relationship between four macro variables (consumer price index, industrial production, exchange rate and number of tourist arrivals) and a stock index composed of Croatian hospitality companies. After applying Granger-causality tests based on the VAR methodology, results suggest that only consumer price index Granger-cause stock returns in the hospitality industry in the observed period from July 2008 to July 2018. Further analysis through impulse response function indicates that the impulse responses of inflation meet expectations in terms of the direction of impact. In the second month, stock prices react negatively to shock, implying that higher inflation causes negative stock price returns. After applying the variance decomposition method, a very low explanatory power of consumer price index on stock returns in the hospitality industry was revealed. This paper contributes to the existing literature on the topic of the impact of macro-economic variables on hospitality stock returns by extending the scope to Croatia and by testing a different set of variables compared to those from previous studies.